The pro- and anticoagulant role of blood-borne phagocytes in patients with acute coronary syndrome - Leers, Math P. G.; Keuren, Jeffrey F. W.; Frissen, Mick E. P. W.; Huts, Mark; Kragten, Johannes A.; Jie, Kon-Siong G. (Thrombosis and Haemostasis, 2013)
This study was performed to gain further insight in pro- and anticoagulant characteristics of leukocytes in acute coronary syndrome (ACS). For this purpose, patients presenting on the emergency department (ED) with anginal chest pain were included in this study. In peripheral blood, procoagulant tissue factor (TF) expression was measured in the different blood-borne phagocytes, i.e. neutrophilic granulocytes and the three different monocyte subsets based on expression of CD14 and CD16. Simultaneously, intracellular presence of platelet-(CD41) and/or endothelial cell-remnants (CD62e) was analysed in these different leukocyte subsets. Neutrophils showed a weak intracellular staining of CD62e and CD41 that increased with severity of ACS. Monocytes, and especially the classical (CD14++CD16-) and intermediate monocytes (CD14++CD16+) showed a clear and significant increase in intracellular CD41-staining after coronary damage. The different monocyte subsets showed an increase in expression of TF in severe ACS. Finally, it appeared that also neutrophils showed a significant increase in expression of TF on their membrane. In conclusion, this study showed an increased intracellular staining in blood-borne phagocytes for CD62e and CD41 in patients with ACS compared to non-cardiac related control patients. This indicates that at least in the acute phase of ACS phagocytosis of platelet and endothelial cell-remnants is increased. These data support the recent hypothesis that neutrophils protect against further thrombotic processes by clearing platelet and endothelial cell-remnants. In addition, this study shows that the different monocyte subsets are also involved in this process. Furthermore, both monocytes and neutrophils show increased TF expression in ACS.
Keywords: Platelets; endothelium; microparticles; phagocytosis; flow cytometry